الخصائص المنهجية للتفسير المظهري وأثره في مدرسة التفسير في شبه القارة : Methodological Characteristics of Al tafseer Al mazhari and Its Impact in the School of Interpretation in the subcontinent - Dr Zaib Un Nisa; Dr Mirza Mujahid Ahmad Baig (Al Manhal Research Journal, 2024)
(Al-Tafsir Al-Mazhari) is one of those moderate and practiced interpretations that has gained fame in the academic world due to its balanced approach, moderation, and balance between criticism and consideration. The tools of this interpretation are also easy to understand, structured, and clear in meaning. It is characterized by the fact that the interpreter gathers many opinions, explains the most correct of the opinions and proves it. He relies on mentioning them collectively rather than individually. It attempts to provide a summary that preserves understanding and comprehension of the interpretation in a good manner. If we study Al Tafseer Al Mazhari, we find that the author of the interpretation has relied upon books of tafsir, hadith and it's various fields, jurisprudence, biography, history, Sufism, etc. He spent many long years in its compilation, resulting in a voluminous encyclopedia that includes a summary of his knowledge, research, and experiences.